Temperature Rise and Wear Characteristics of Mechanical Seal Face of Deep-Sea Equipment Under Alternating Conditions - ZHENG Simin, TENG Liming, ZHAO Wenjing, JIANG Jinbo, WANG Mengjiao, PENG Xudong (Shanghai Jiaotong Daxue xuebao, 2023)
In order to study the effects of deep-sea complex and severe working conditions on the power device of deep-sea wading equipment, taking the contacting mechanical seal for deep-sea propeller as the research object, a two-dimensional axisymmetric finite element model is established. The influence of alternating conditions on the temperature rise of seal face is explored. The pseudo-real condition test of the mechanical seal is conducted on a self-built test rig, and the temperature rise of seal face is monitored. The surface morphology and wear characteristics are measured and analyzed. The results show that the alternating conditions have a significant influence on the temperature field of the seal ring, and the temperature rise of seal face shows an obvious alternating transient characteristic. After the alternating condition test, the end face roughness of the rotating ring increases significantly. The transient working condition makes the contact state between the seal faces unstable. Abrasive wear occurs on the end face, with obvious pits and densely distributed furrows of different depths. The alternating speed has a greater influence on the temperature rise and wear of the end face than that of the alternating medium pressure. The numerical simulation results are in good agreement with the experimental results, which provides a necessary theoretical guidance and experimental basis for the structural design of the mechanical seal of the deep-sea propeller.